Organisational Practice in the job centre - Variance or Homogeneity? - Navina Roman (Social Work and Society, 2015)
The introduction of"modern labour market services" and associated new forms of intervention and job placement (known colloquially in Germany as"Hartz") have generated a need for research not only into the concrete practice of job placement, but also into the"job centre organisation" and its organisational structure. Statutory impact research Impact research (which is required by law) can reveal neither the actual daily interaction and communication processes occurring in the job centres, nor the concrete organisational practice which sets in either before or after the benefits processes. What remains is what lies in-between - in a"black box" that provokes the question of how, after the reforms, the job centre produces itself organisationally. This deficit is surprising, because a significant section of the Agenda 2010 reforms focussed precisely on processes of organisational change in the employment office and were inspired by the formula of the"third way" as proposed by sociologists (above all Anthony Giddens) on the basis of their analyses of reflexive modernity. Against this background of organisational change and the merger of different strands social benefits, this contribution examines from the perspective of ethnographic analysis the emergence of a (new) organisation through social (organisational) practice. Do organisational learning processes lead to productive results or can they produce a standardisation of organisational practice and culture(s)? The contribution investigates employment service organisation as"lived" practice from the perspective of the actors, using the example of a specific job centre. Empirically, the contribution is based in a case study that drew on a small quantitative staff survey. The results show clearly that - contrary to the expectation that hybridity will be characterised by different (organisational) cultures and historical layerings in organisational processes - organisational learning processes lead not to dynamic development. Accordingly, the job centre suffers not from too much variance but from a standardisation of organisational practice which leads to a lived practice of"rule of the bureaucracy" in the Weberian tradition.